Anti-Mullarian hormone versus day three follicular stimulating hormone and antral follicular count as a predictor for ovarian response to stimulation - Ali AL-Naser, Alaa Hussien; Mileehim , Israa Jabbar (International Journal of Psychosocial Rehabilitation, 2020)
Back ground: Recently, a new marker, the anti-mullarian hormone (AMH), has been evaluated as a marker of ovarian response. Since the number of ovarian follicles decline with increasing age, AMH level might be used as a marker for ovarian aging, and serum AMH can be measured at frequent time-points during menstrual cycle, suggesting the complete absence of fluctuation. Aim of study: To evaluate wither anti-Mullarian hormone is a better predictor of ovarian response to stimulation in comparism to day 3 follicular stimulating hormone (FSH) and antral follicular count (AFC).Subjects and methods: This study was carried out at Bint AL-Huda teaching hospital in Thi-qar and Basrah IVF center during the period from 1st January 2012-1st January 2013 including 60 women with infertility caused by anovulation, and they were assesd by doing day 3 FSH, AMH and AFC, then they were subjected to ovulation induction treatment using clomiphene citrate 50 mg three times daily from day 2-6 of menstrual cycle and then assess at day 7 with transvaginal u/s and serum oestradiol level for the size and numbers of mature graffian follicle, if they were not responding to clomiphene citrate tablet they were given 3 ampules of follicular stimulating hormone ( follitropin beta ) (50iu/0.5ml) at day 7, 8, and 9 of menstrual cycle, on day 10-11 of menstrual cycle the MGF was assessed for the numbers and size and serum sample obtained for measurement of oestradiol level. The data were analyzed by using t test, pearson correlation, regression coefficient and area under receiver operating curve (ROC) was calculating as measure of predictive accuracy.Result: From total (60) women. (11) patients have no ovarian response and (49) patients have normal ovarian response, the non responders group have significantly lower day 3 antral follicular count (AFC) 5 with p value=0.004, and also the non responders group had significantly low anti-Mullarian hormone level (AMH) (0.1±0.1) compare with normal responders the AMH level (1.2±0.6) with p value=0.001, follicular stimulating hormone level (FSH) was significantly higher in non responders (7.6±4.2) compare to normal responders the FSH level was (4.7±1.5) with p value=0.001,and the mean day 11 MGF count and E2 was higher in normal responders group compared with non responders group with p value=0.001. There was a ppositive correlation between AMH and AFC with MGF count while the correlation between FSH and MGF was negative. Multivariate analysis of the variables that predict good ovarian response to ovulation induction treatment demonstrate that the biochemical variable AMH was the most significant predictor as (R2=64. 9%).The AMH level was addressed as the only significant variable in determination of MGF numbers as AMH with a cut-off value >0.37ng/ml has area under the curve (accuracy)(0.96%) with p value